Integral Calculus

Download as pdf or txt
Download as pdf or txt
You are on page 1of 12

MODULE 3

INTEGRAL CALCULUS
Integral Calculus: Beta and Gamma functions–interrelation-evaluation of
integrals using gamma and beta functions; error function-properties.
Multiple Integrals- Double integrals – Change of order of integration –
Double integrals in polar coordinates – Area enclosed by plane curves,
evaluation of triple integrals-change of variables between Cartesian and
cylindrical and spherical polar co-ordinates.

Beta and Gamma Function


To evaluate certain definite integral which are either difficult or impossible to evaluate by
various known methods of integration, we use Beta and Gamma function.
Definition:
1

𝛽(𝑚, 𝑛) = ∫ 𝑥 m−1 (1 − 𝑥)𝑛−1 𝑑𝑥 (𝑚, 𝑛 > 0)


0

is called Beta function.


Γ(𝑛) = ∫ 𝑒 −𝑥 𝑥 𝑛−1 𝑑𝑥 (𝑛 > 0)


0

is called Gamma function.


Alternative Forms:
𝜋/2

𝛽(𝑚, 𝑛) = 2 ∫ sin2𝑚−1 𝜃 cos 2𝑛−1 𝜃𝑑𝜃


0

2
Γ(𝑛) = 2 ∫ 𝑒 −𝑥 𝑥 2𝑛−1 𝑑𝑥
0

Properties:
1. 𝛽(𝑚, 𝑛) = 𝛽(𝑛, 𝑚)
2. Γ(𝑛 + 1) = 𝑛Γ(𝑛)
Γ(𝑛) = (𝑛 − 1)Γ(𝑛 − 1), 𝑛 ≠ 1
3. Γ(𝑛 + 1) = 𝑛! if 𝑛 is positive integer.
(𝑛 − 1)! 𝑛 𝑖𝑠 𝑝𝑜𝑠𝑖𝑡𝑖𝑣𝑒 𝑖𝑛𝑡𝑒𝑔𝑒𝑟
4. Γ(𝑛) = { Γ(𝑛+1)
𝑛 𝑖𝑠 𝑛𝑒𝑔𝑎𝑡𝑖𝑣𝑒 𝑖𝑛𝑡𝑒𝑔𝑒𝑟.
𝑛

1
Relationship between Beta and Gamma Function
Γ(𝑚)Γ(𝑛)
𝛽(𝑚, 𝑛) =
Γ(𝑚 + 𝑛)

1. Prove that 𝚪(𝟏/ 𝟐)= √𝝅


Γ(𝑚)Γ(𝑛)
Proof: w.k.t 𝛽(𝑚, 𝑛) =
Γ(𝑚+𝑛)
1
Put 𝑚 = 𝑛 =
2
1 1
1 1 Γ( )Γ( )
𝛽 ( , ) = 21 12
2 2 Γ( + ) 2 2

1 2
[Γ ( )]
2
=
Γ(1)
1 1 1 2
𝛽 ( , ) = [Γ ( )] − − − −(1), (since, Γ(1) = 1)
2 2 2
1 1 𝜋/2
Consider, 𝛽 ( , ) = 2 ∫0 sin0 𝜃 cos 0 𝜃𝑑𝜃
2 2
𝜋/2
= 2 ∫0 (1)(1)𝑑𝜃
𝜋/2 𝜋
= 2[𝜃]0 = 2 [ − 0] = 𝜋
2

1 2
Hence, (1) gives [Γ ( )] = 𝜋.
2
1
Therefore, we get Γ ( ) = √𝜋.
2

Problems using Gamma Function



1. Evaluate ∫0 𝑥 3/2 𝑒 −𝑥 𝑑𝑥
3

Solution: Let 𝐼 = ∫0 𝑥 2 𝑒 −𝑥 𝑑𝑥
5

= ∫0 𝑥 2−1 𝑒 −𝑥 𝑑𝑥
5 3
= Γ ( ) = Γ ( + 1)
2 2
3 3
= Γ( ) (since, Γ(𝑛 + 1) = 𝑛Γ(𝑛))
2 2

2
3 1 31 1 3
= Γ ( + 1) = Γ ( ) = √π
2 2 22 2 4


2. Evaluate ∫0 𝑥 1/4 𝑒 −√𝑥 𝑑𝑥

Solution: Let 𝐼 = ∫0 𝑥 1/4 𝑒 −√𝑥 𝑑𝑥 ------- (1)

Put, 𝑡 = √𝑥
𝑥 = 𝑡 2 . Then 𝑑𝑥 = 2𝑡𝑑𝑡.
If, 𝑥 = 0 ⇒ 𝑡 = 0 and 𝑥 = ∞ ⇒ 𝑡 = ∞
Therefore, the equation (1) becomes

𝐼 = ∫ 𝑒 −𝑡 (𝑡 2 )1/4 2𝑡𝑑𝑡
0
∞ ∞

= 2 ∫ 𝑒 −𝑡 𝑡 1/2 𝑡𝑑𝑡 = 2 ∫ 𝑒 −𝑡 𝑡 3/2 𝑑𝑡


0 0

5 5 3
= 2 ∫ 𝑒 −𝑡 𝑡 2−1 𝑑𝑡 = 2Γ ( ) = 2Γ ( + 1)
2 2
0
3 3
= 2 × Γ( ) (𝑠𝑖𝑛𝑐𝑒, Γ(𝑛 + 1) = 𝑛Γ(𝑛))
2 2
1 1 1 3
= 3Γ ( + 1) = 3 × Γ ( ) = √π
2 2 2 2

1
3. Evaluate ∫0 √−𝑙𝑜𝑔𝑥 𝑑𝑥
1
Solution: Let 𝐼 = ∫0 √−𝑙𝑜𝑔𝑥 𝑑𝑥

Put 𝑡 = −𝑙𝑜𝑔𝑥 ⇒ −𝑡 = 𝑙𝑜𝑔𝑥


𝑒 −𝑡 = 𝑒 𝑙𝑜𝑔𝑥
𝑒 −𝑡 = 𝑥 ---------- (1)
Then −𝑒 −𝑡 𝑑𝑡 = 𝑑𝑥
If 𝑥 = 0, equation (1) becomes 𝑒 −𝑡 = 0 ⇒ 𝑡 = ∞
If 𝑥 = 1, equation (1) becomes 𝑒 −𝑡 = 1 ⇒ 𝑡 = 0.
0 −𝑡 1 ∞ −𝑡 3−1
Therefore, 𝐼= − ∫∞ 𝑒 𝑡 2 𝑑𝑡 = ∫0 𝑒 𝑡 2 𝑑𝑡

3
3 1 1 1
= Γ ( ) = Γ ( + 1) = Γ ( ) ( because Γ(𝑛 + 1) = 𝑛Γ(𝑛))
2 2 2 2
1
= √π
2
1 1
So, ∫0 √−𝑙𝑜𝑔𝑥𝑑𝑥 = √π
2

Practice Problems
1 1 3
1. Evaluate∫0 𝑥 5 (log ( )) 𝑑𝑥.
𝑥
1
2. Evaluate ∫0 (𝑥𝑙𝑜𝑔𝑥)4 𝑑𝑥

Problems using beta function


3 1
1
1. Evaluate ∫0 𝑥 2 (1 − 𝑥)2 𝑑𝑥 using beta function.
1 3 1
Solution. Let 𝐼 = ∫0 𝑥 2 (1 − 𝑥) 𝑑𝑥 2

1 5 3
= ∫ 𝑥 2 −1 (1 − 𝑥)2−1 𝑑𝑥
0
5 3 5 3
5 3 Γ( ) Γ( ) Γ( ) Γ( )
2 2 2 2
= 𝛽( , ) = 5 3
=
2 2 Γ (2 + 2) Γ(4)

3 1 3 3 1 1
Γ ( + 1) Γ ( + 1) Γ( ) Γ( )
2 2 2 2 2 2
= =
Γ(4) Γ(4)
3 1 1 3 1 1
Γ ( + 1) √π Γ ( ) √π
2 2 2 4 2 2
= =
3! 6
3
√π√π 𝜋
8
= =3 .
6 48
3 5
4
2. Evaluate ∫0 𝑥 2 (4 − 𝑥)2 𝑑𝑥 .
3 5
4
Solution. Let 𝐼 = ∫0 𝑥 2 (4 − 𝑥)2 𝑑𝑥

Put 𝑥 = 4𝑠𝑖𝑛2 𝜃 ----------(1) ⇒ 𝑑𝑥 = 4 × 2𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃


= 8 𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
If 𝑥 = 0, (1) ⇒ 0 = 4𝑠𝑖𝑛2 𝜃, i.e., 𝜃 = 0.
π
If 𝑥 = 4, (1)⇒ 4 = 4𝑠𝑖𝑛2 𝜃, i.e., 𝜃 = .
2
4
𝜋 3 5
Therefore, 𝐼 = ∫0 (4𝑠𝑖𝑛2 𝜃)2 (4 − 4𝑠𝑖𝑛2 𝜃)2 8 𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
2

𝜋
2 3 5
= ∫ (22 𝑠𝑖𝑛2 𝜃)2 [4(1 − 𝑠𝑖𝑛2 𝜃)]2 8 𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
0
𝜋
2 5
= ∫ 23 𝑠𝑖𝑛3 𝜃 25 (𝑐𝑜𝑠 2 𝜃)2 8 𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
0
𝜋
2
= ∫ 8𝑠𝑖𝑛3 𝜃 32 𝑐𝑜𝑠 5 𝜃 8 𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
0
𝜋
2
= 2048 ∫ 𝑠𝑖𝑛4 𝜃 𝑐𝑜𝑠 6 𝜃𝑑𝜃
0

1 4+1 6+1
= 2048 𝛽( , )
2 2 2
5 7
5 7 Γ( )Γ( )
= 1024𝛽 ( , ) = 1024 25 72
2 2 Γ( + ) 2 2
3 5 3 3 5 5
Γ ( + 1) Γ ( + 1) Γ( ) Γ( )
2 2 2 2 2 2
= 1024 12
= 1024
Γ(2) Γ(6)

31 1 53 3 31 1 53 3
Γ( ) Γ( ) Γ( ) Γ( )
22 2 22 2 22 2 22 2
= 1024 = 1024
5! 120
31 1 53 1 31 531 1
Γ ( ) Γ ( + 1) √π 2 2 2 Γ (2)
22 2 22 2 22
= 1024 = 1024
120 120
3 15
4
√π 8 √π
= 128 = 12𝜋.
15
𝜋
3. Evaluate ∫02 √𝑡𝑎𝑛𝜃𝑑𝜃
𝜋
√𝑠𝑖𝑛𝜃
Solution: 𝐼 = ∫02 𝑑𝜃
√𝑐𝑜𝑠𝜃
𝜋
2 1 1
= ∫ 𝑠𝑖𝑛2 𝜃 𝑐𝑜𝑠 −2 𝜃𝑑𝜃
0
1 −1 3 1
1 +1 +1 1
= 𝛽 (2 , 2
) = 𝛽(2 , 2)
2 2 2 2 2 2

5
3 1
1 3 1 1 Γ (4) Γ (4)
= 𝛽( , ) =
2 4 4 2 Γ ( 3 + 1)
4 4
3 1 3 1
1 Γ (4) Γ (4) 1 Γ (4) Γ (4)
= =
2 Γ(1) 2 0!
3 1
1 Γ (4) Γ (4) 1 3 1
= = Γ( )Γ( )
2 1 2 4 4
1 𝜋 3 1
= 𝜋√2 = (𝑠𝑖𝑛𝑐𝑒, Γ ( ) Γ ( ) = 𝜋√2)
2 √2 4 4
1 𝑥2 1 𝑑𝑥 𝜋
4. Prove that ∫0 𝑑𝑥 ∫0 =
√1−𝑥 4 √1+𝑥 4 4 √2

1 𝑥2
Proof: Let 𝐼1 =∫0 𝑑𝑥
√1−𝑥 4
1
4 2
Put 𝑥 = 𝑠𝑖𝑛 𝜃 ⇒ 𝑥 = 𝑠𝑖𝑛 𝜃 ------------- (1) 2

1 1
𝑑𝑥 = 𝑠𝑖𝑛−2 𝜃 cos 𝜃𝑑𝜃
2
1
If 𝑥 = 0, from (1), we get 0 = (𝑠𝑖𝑛𝜃)2 ⇒ 𝜃 = 0
1
𝜋
If 𝑥 = 1, from (1), we get 1 = (𝑠𝑖𝑛𝜃) ⇒ 𝜃 = 2
2

𝜋 1
1
(𝑠𝑖𝑛2 𝜃)2 1
Therefore, 𝐼1 =∫0 2 𝑠𝑖𝑛−2 𝜃 cos 𝜃𝑑𝜃
√1−𝑠𝑖𝑛2 𝜃 2
𝜋 1
1 𝑠𝑖𝑛𝜃
= ∫02 𝑠𝑖𝑛−2 𝜃 cos 𝜃𝑑𝜃
2 √𝑐𝑜𝑠 2 𝜃

𝜋 1 𝜋 1
1 𝑠𝑖𝑛 2𝜃 1
= ∫0 2 cos 𝜃𝑑𝜃 = ∫ 𝑠𝑖𝑛2 𝜃𝑑𝜃
2
2 cos 𝜃 2 0
1
11 +1 0+1 1 3 1
= 𝛽 (2 , ) = 𝛽( , )
22 2 2 4 4 2

1 𝑑𝑥
Consider 𝐼2 = ∫0
√1+𝑥 4
1
Put 𝑥 4 = 𝑡𝑎𝑛2 𝜃 ⇒ 𝑥 = 𝑡𝑎𝑛2 𝜃 ------------ (2)
1
1
𝑑𝑥 = 𝑡𝑎𝑛−2 𝜃𝑠𝑒𝑐 2 𝜃𝑑𝜃
2
1
If 𝑥 = 0, from (2), we get 0 = (𝑡𝑎𝑛𝜃)2 ⇒ 𝜃 = 0

6
1
𝜋
If 𝑥 = 1, from (2), we get 1 = (𝑡𝑎𝑛𝜃)2 ⇒ 𝜃 =
4
1
𝜋 1𝑡𝑎𝑛−2 𝜃𝑠𝑒𝑐 2 𝜃𝑑𝜃
Therefore, 𝐼2 =∫ 42
0 √1+𝑡𝑎𝑛2 𝜃

𝜋 1 𝜋 1
− −
1 𝑡𝑎𝑛 2 𝜃𝑠𝑒𝑐 2 𝜃 1 𝑠𝑖𝑛 2 𝜃 1
= ∫ 0
4 𝑑𝜃= ∫0 4
1 𝑑𝜃
2 √𝑠𝑒𝑐 2 𝜃 2 −
cos 2 𝜃
𝑐𝑜𝑠 𝜃

𝜋 1 1 𝜋
1 4 𝑠𝑖𝑛−2 𝜃 cos −2 𝜃 𝑑𝜃 =
1 1
= ∫ ∫4 𝑑𝜃
2 0 2 0 √𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃
𝜋
1 1
= ∫0 4 𝑑𝜃 (since, 𝑠𝑖𝑛2𝜃 = 2𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃)
2 𝑠𝑖𝑛2𝜃

2

𝜋
1 √2
= ∫0 4 𝑑𝜃
2 √𝑠𝑖𝑛2𝜃
𝑑𝑢
Put 2𝜃 = 𝑢 ⇒ 2𝑑𝜃 = 𝑑𝑢 ⇒ 𝑑𝜃 =
2
𝜋 𝜋 𝜋
If 𝜃 = 0, 𝑢 = 0 and 𝜃 = , 𝑢 = 2 ( ) =
4 4 2
𝜋 1 𝜋
√2 2 1 𝑑𝑢 √2 2 −
= ∫ = ∫ 𝑠𝑖𝑛 2 𝑢𝑐𝑜𝑠 0 𝑢𝑑𝑢
2 0 √𝑠𝑖𝑛𝑢 2 4 0
1
1 1 − +1 0+1 1 1 1
2
= 𝛽( , )= 𝛽( , )
2√2 2 2 2 4√ 2 4 2

1 𝑥2 1 𝑑𝑥 1 3 1 1 1 1
Therefore, ∫0 𝑑𝑥 ∫0 = 𝛽( , ) 𝛽( , )
√1−𝑥 4 √1+𝑥 4 4 4 2 4 √ 2 4 2

1 3 1 1 1
= 𝛽( , )𝛽( , )
16√2 4 2 4 2
3 1 1 1
1 𝛤( )𝛤( ) 𝛤( )𝛤( )
4 2 4 2
= 3 1 1 1
16√2 𝛤(4+2) 𝛤(4+2)

3 1 1 1
1 𝛤( )𝛤( )𝛤( )𝛤( )
4 2 4 2
= 5 3
16√2 𝛤 (4) 𝛤 (4)
1 1
1 √𝜋𝛤 (4) √𝜋 𝜋 𝛤( )
4
= =
16√2 𝛤 (1 + 1) 16√2 1 𝛤 (1)
4 4 4

4𝜋 𝜋
= =
16√2 4√2
∞ 8 ∞ 4 𝜋
5.Show that ∫0 𝑥𝑒 −𝑥 𝑑𝑥 ∫0 𝑥 2 𝑒 −𝑥 𝑑𝑥 =
16√2

7
∞ 8
Solution: Let 𝐼1 = ∫0 𝑥𝑒 −𝑥 𝑑𝑥

Put 𝑥 8 = 𝑡
8𝑥 7 𝑑𝑥 = 𝑑𝑡
𝑑𝑡
𝑥𝑑𝑥 = 6
8𝑥
𝑑𝑡
𝑥𝑑𝑥 = 1
8(𝑡 8 )6
𝑑𝑡
𝑥𝑑𝑥 = 3
8𝑡 4
If 𝑥 = 0 ⇒ 𝑡 = 0
If 𝑥 → ∞ ⇒ 𝑡 → ∞.
∞ 𝑑𝑡
Therefore, 𝐼1 = ∫0 𝑒 −𝑡 3
8𝑡 4

1 ∞ −𝑡 −3
= ∫ 𝑒 𝑡 4 𝑑𝑡
8 0
1 ∞ 1
= ∫ 𝑒 −𝑡 𝑡 4−1 𝑑𝑡
8 0
1 1
= 𝛤( )
8 4

∞ 4
Let 𝐼2 = ∫0 𝑥 2 𝑒 −𝑥 𝑑𝑥

Put 𝑥 4 = 𝑢
4𝑥 3 𝑑𝑥 = 𝑑𝑢
𝑑𝑢
𝑥 2 𝑑𝑥 =
4𝑥
𝑑𝑢
𝑥 2 𝑑𝑥 = 1
4 (𝑢4 )

If 𝑥 = 0 ⇒ 𝑡 = 0
If 𝑥 → ∞ ⇒ 𝑡 → ∞.
∞ 𝑑𝑢
Therefore, 𝐼2 = ∫0 𝑒 −𝑢 1
4𝑢4

1 ∞ −𝑢 −1
= ∫ 𝑒 𝑢 4 𝑑𝑢
4 0
8
1 ∞ −𝑢 3−1
= ∫ 𝑒 𝑢4 𝑑𝑢
4 0
1 3
= 𝛤( )
4 4
Therefore,
∞ ∞
−𝑥 8 4 1 1 1 3 1
∫ 𝑥𝑒 𝑑𝑥 ∫ 𝑥 2 𝑒 −𝑥 𝑑𝑥 = 𝛤( ) 𝛤( ) = 𝜋√2
0 0 8 4 4 4 32
𝜋√2√2 𝜋(2) 𝜋
= = = .
32√2 32√2 16√2

Multi Variable Calculus (Integration)


Let 𝑓(𝑥, 𝑦) be a continuous and a single valued function of 𝑥 and 𝑦 over the region of
integration 𝑅 and be enclosed by the surface 𝑆.
Then the double integral of 𝑓(𝑥, 𝑦) over 𝑅 is defined by

∬ 𝑓(𝑥, 𝑦)𝑑𝑥𝑑𝑦
𝑅

Note:
I. ∬𝑅 𝑑𝑥𝑑𝑦 represents area of the region 𝑅 in Cartesian form.
II. ∬𝑅 𝑟𝑑𝑟𝑑𝜃 represents area of the region 𝑅 in polar form.

Similarly, the triple integral of 𝑓(𝑥, 𝑦, 𝑧) over the region 𝑉 is defined by

∭ 𝑓(𝑥, 𝑦, 𝑧)𝑑𝑥𝑑𝑦𝑑𝑧
𝑉

III. ∭𝑉 𝑓(𝑥, 𝑦, 𝑧)𝑑𝑥𝑑𝑦𝑑𝑧 is volume of a solid.


Problems:
5 𝑥2
Example 1. Evaluate ∫0 ∫0 𝑥(𝑥 2 + 𝑦 2 )𝑑𝑦𝑑𝑥
5 𝑥2
Solution: Let 𝐼 = ∫0 ∫0 𝑥(𝑥 2 + 𝑦 2 )𝑑𝑦𝑑𝑥
5 𝑥2
= ∫ [∫ 𝑥(𝑥 2 + 𝑦 2 )𝑑𝑦] 𝑑𝑥
0 0

5 𝑥2 𝑥2
= ∫ [𝑥 3 ∫ 𝑑𝑦 + 𝑥 ∫ 𝑦 2 𝑑𝑦] 𝑑𝑥
0 0 0
9
5 𝑥2
3 [𝑦] 𝑥 2
𝑦3
= ∫ [𝑥 0 + 𝑥 [ ] ] 𝑑𝑥
0 3 0
5 (𝑥 2 )3
3 [𝑥 2
= ∫ [𝑥 − 0] + 𝑥 [ − 0]] 𝑑𝑥
0 3
5
𝑥7 5
= ∫ [𝑥 + ] 𝑑𝑥
0 3
5
𝑥6 𝑥8 56 58 0 0 56 5 8
=[ + ] =[ + − ( + )] = [ + ].
6 3×8 0 6 24 6 24 6 24

Hence

5 𝑥2
2 2 )𝑑𝑦𝑑𝑥
56 58
∫ ∫ 𝑥(𝑥 + 𝑦 =[ + ]
0 0 6 24

1 √1−𝑦 2
Example 2. Evaluate ∫0 ∫0 𝑥 3 𝑦𝑑𝑥𝑑𝑦
1 √1−𝑦 2
Solution: Let 𝐼 = ∫0 ∫0 𝑥 3 𝑦𝑑𝑥𝑑𝑦
1 √1−𝑦 2
= ∫ 𝑦 [∫ 𝑥 3 𝑑𝑥 ] 𝑑𝑦
0 0

1 √1−𝑦 2
x4
= ∫ 𝑦[ ] 𝑑𝑦
0 4 0
4
1
(√1 − 𝑦 2 ) 1 1 4
= ∫ 𝑦[ − 0] 𝑑𝑦 = ∫ 𝑦 [(√1 − 𝑦 2 ) ] 𝑑𝑦
0 4 4 0

1 1 2 )2 ]𝑑𝑦
1 1
= ∫ 𝑦[(1 − 𝑦 = ∫ 𝑦[(𝑦 4 + 1 − 2𝑦 2 )]𝑑𝑦
4 0 4 0
1
1 1 5 3
1 𝑦6 𝑦2 𝑦4
= ∫ [(𝑦 + 𝑦 − 2𝑦 )]𝑑𝑦 = [( + − 2 )]
4 0 4 6 2 4 0

1 1 6 12 14 0 0 0
= [( + − 2 ) − ( + − )]
4 6 2 4 6 2 2

10
1 16 12 14 1
= [( + − 2 )] =
4 6 2 4 24
1 √1−𝑦 2 1
Hence ∫0 ∫0 𝑥 3 𝑦𝑑𝑥𝑑𝑦 = .
24

𝑐 𝑏 𝑎
6. Evaluate ∫−𝑐 ∫−𝑏 ∫−𝑎(𝑥 2 + 𝑦 2 + 𝑧 2 )𝑑𝑧𝑑𝑦𝑑𝑥
𝑐 𝑏 𝑎
Solution: 𝐼 = ∫𝑥=−𝑐 ∫𝑦=−𝑏 ∫𝑧=−𝑎(𝑥 2 + 𝑦 2 + 𝑧 2 )𝑑𝑧𝑑𝑦𝑑𝑥
𝑐 𝑏 𝑎
2 2
𝑧3
=∫ ∫ [𝑥 𝑧 + 𝑦 𝑧 + ] 𝑑𝑦𝑑𝑥
𝑥=−𝑐 𝑦=−𝑏 3 −𝑎
𝑐 𝑏
2 [𝑎
𝑎3 𝑎3
=∫ ∫ {𝑥 − (−𝑎)] + 𝑦 2 [𝑎 − (−𝑎)] + [ − (− )]} 𝑑𝑦𝑑𝑥
𝑥=−𝑐 𝑦=−𝑏 3 3
𝑐 𝑏
2𝑎3 2 2
=∫ ∫ [2𝑎𝑥 + 2𝑎𝑦 + ] 𝑑𝑦𝑑𝑥
𝑥=−𝑐 −𝑏 3
𝑐 𝑏
2𝑎𝑦 3 2𝑎3 𝑦 2
=∫ [2𝑎𝑥 𝑦 + + ] 𝑑𝑥
𝑥=−𝑐 3 3 −𝑏
𝑐
2 [𝑏
𝑏3 𝑏3 2𝑎3
=∫ {2𝑎𝑥 − (−𝑏)] + 2𝑎 [ − (− )] + [𝑏 − (−𝑏)]} 𝑑𝑥
𝑥=−𝑐 3 3 3
𝑐
2𝑏 3 2𝑎3 2
=∫ [2𝑎𝑥 . 2𝑏 + 2𝑎. + . 2𝑏] 𝑑𝑥
𝑥=−𝑐 3 3
𝑐 𝑐
2
4𝑎𝑏 3 4𝑎3 𝑏 4𝑎𝑏𝑥 3 4𝑎𝑏 3 𝑥 4𝑎3 𝑏𝑥
=∫ [4𝑎𝑏𝑥 + + ] 𝑑𝑥 = [ + + ]
𝑥=−𝑐 3 3 3 3 3 −𝑐

𝑐3 𝑐3 4𝑎𝑏 3 4𝑎3 𝑏
= 4𝑎𝑏 [ − (− )] + [𝑐 − (−𝑐)] + [𝑐 − (−𝑐)]
3 3 3 3
2𝑐 3 4𝑎𝑏 3 4𝑎3 𝑏 8𝑎𝑏𝑐 3 8𝑎𝑏 3 𝑐 8𝑎3 𝑏𝑐
= 4𝑎𝑏. + . 2𝑐 + 2𝑐 = + +
3 3 3 3 3 3
8𝑎𝑏𝑐(𝑐 2 +𝑏2 +𝑎2 )
=
3
8𝑎𝑏𝑐(𝑎2 +𝑏2 +𝑐 2 )
Thus, 𝐼= .
3
𝑎 𝑥 𝑥+𝑦
7. Evaluate ∫𝑥=0 ∫𝑦=0 ∫𝑧=0 𝑒 𝑥+𝑦+𝑧 𝑑𝑧𝑑𝑦𝑑𝑥
𝑎 𝑥 𝑥+𝑦
Solution: Let 𝐼 = ∫𝑥=0 ∫𝑦=0 ∫𝑧=0 𝑒 𝑥+𝑦+𝑧 𝑑𝑧𝑑𝑦𝑑𝑥

11
𝑎 𝑥 𝑥+𝑦 𝑎 𝑥
𝑥+𝑦 𝑧 𝑥+𝑦
=∫ ∫ ∫ 𝑒 𝑒 𝑑𝑧𝑑𝑦𝑑𝑥 = ∫ ∫ 𝑒 𝑥+𝑦 [𝑒 𝑧 ]𝑧=0 𝑑𝑦𝑑𝑥
𝑥=0 𝑦=0 𝑧=0 𝑥=0 𝑦=0
𝑎 𝑥 𝑎 𝑥
𝑥+𝑦 [𝑒 𝑥+𝑦
=∫ ∫ 𝑒 − 1]𝑑𝑦𝑑𝑥 = ∫ ∫ [𝑒 2(𝑥+𝑦) − 𝑒 𝑥+𝑦 ]𝑑𝑦𝑑𝑥
𝑥=0 𝑦=0 𝑥=0 𝑦=0

𝑎 𝑥 𝑎 𝑥
𝑒 2𝑦
2𝑥
= ∫ ∫ [𝑒 𝑒 − 𝑒2𝑦 𝑥+𝑦 ]𝑑𝑦𝑑𝑥 = ∫ {𝑒 [ ] − 𝑒 𝑥 [𝑒 𝑦 ]0𝑥 } 𝑑𝑥
2𝑥
𝑥=0 𝑦=0 𝑥=0 2 0
𝑎 𝑎
𝑒 2𝑥 2𝑥 𝑥 𝑥
𝑒 4𝑥 𝑒 2𝑥
=∫ { [𝑒 − 1] − 𝑒 [𝑒 − 1]}𝑑𝑥 = ∫ [ − − 𝑒 2𝑥 + 𝑒 𝑥 ]𝑑𝑥
𝑥=0 2 𝑥=0 2 2
𝑎 𝑎
𝑒 4𝑥 3 2𝑥 𝑥
𝑒 4𝑥 3𝑒 2𝑥
=∫ [ − 𝑒 + 𝑒 ] 𝑑𝑥 = [ − + 𝑒𝑥]
𝑥=0 2 2 8 4 0

𝑒 4𝑎 3𝑒 2𝑎 𝑎
𝑒 0 3𝑒 0
=[ − +𝑒 ]−[ − + 𝑒 0]
8 4 8 4
𝑒 4𝑎 3𝑒 2𝑎 𝑎
1 3 𝑒 4𝑎 3𝑒 2𝑎 3
= − +𝑒 − + −1= − + 𝑒𝑎 −
8 4 8 4 8 4 8
1
Thus, 𝐼 = [𝑒 4𝑎 − 6𝑒 2𝑎 + 8𝑒 𝑎 − 3]
8

12

You might also like